An Emerging Segment of Functional Legume-Based Beverages: A Review. Issue 5 (4th July 2022) - Nawaz, Malik Adil; Tan, Melvin; Øiseth, Sofia; Buckow, Roman
ABSTRACT: Over the last decade, plant-based beverages have gained popularity amongst consumers who are seeking alternative and environmentally sustainable options to traditional dairy drinks. Whilst these days there is a variety of cereal-based beverages in the market, the legume-based beverage segment is dominated by soy milk products. There is an opportunity to broaden and diversify this segment into other legumes which may offer better functionality and nutrition than soy. However, little is known about the processability, functionality, health benefits and associated health risks of legume-based milk substitutes. Therefore, this review provides an overview of the current knowledge on fundamental processing steps to convert legumes into milk-alternative beverages, what are processing challenges for different legume varieties, how to overcome these challenges and potential quality deficiencies, and what are the opportunities to maximise textural, nutritional and sensory aspects of legume-based beverages. Special attention is given to chickpea and faba beans, a legume segment largely untouched by industry so far.